2014
DOI: 10.4103/0974-9233.142263
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of uveitis at a referral center in Iraq

Abstract: Purpose:To determine the etiologies of uveitis and the causes of visual loss in uveitis patients at a referral center in Baghdad, Iraq.Patients and Methods:A 4-year prospective study was performed at the uveitis clinic at Ibn Al-Haetham teaching eye hospital in Baghdad, Iraq. Referral cases of active uveitis were included. A complete ophthalmic examination was performed in all cases. If clinical picture did not indicate a specific etiology, patients were sent for a routine set of tests while ancillary tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 19 publications
4
16
0
2
Order By: Relevance
“…Prevalence of TB as an etiology of uveitis has varied from 0.5% in the USA, 12 4% in the People’s Republic of China, 13 6.31% in Italy, 14 6.9% in Japan, 15 9.86% in north India, 16 10.5% in Saudi Arabia, 17 and 11.4% in Iraq where TB is endemic. 18 …”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of TB as an etiology of uveitis has varied from 0.5% in the USA, 12 4% in the People’s Republic of China, 13 6.31% in Italy, 14 6.9% in Japan, 15 9.86% in north India, 16 10.5% in Saudi Arabia, 17 and 11.4% in Iraq where TB is endemic. 18 …”
Section: Clinical Featuresmentioning
confidence: 99%
“… 33 A previous study conducted in Iraq, showed a high sensitivity and specificity of strongly positive TST (more than 14 mm area of induration/necrosis) for ocular TB in the Iraqi population. 18 …”
Section: Tuberculin Skin Testingmentioning
confidence: 99%
“…55,131,150,153 Uveitis can occur at any age, but the mean age of incidence is between 30 to 40 years in most studies. 12,55,131,150,153,188,248 About 60%–80% of uveitis occurs between the ages of 20 to 50 years. 242 In terms of anatomic classification, anterior uveitis is the most common form of uveitis, followed by panuveitis, posterior uveitis, and intermediate uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of anterior uveitis, panuveitis, posterior uveitis, and intermediate uveitis is reported to be 24.5%–52.3%, 11.8%–52.9%, 7.1%–46.0%, and 6.3%–19.3%, respectively, in several studies. 12,55,131, 150,153,188,248 The causes of posterior uveitis can be infectious (bacterial, viral, fungal, and parasitic), noninfectious (autoimmune or associated with a systemic disease), or part of a masquerade syndrome. 53 A significant proportion of the cases of posterior uveitis are infectious (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation